2015
DOI: 10.3329/pa.v25i0.24066
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Paracoccus marginatus in Bangladesh and its control strategies in the fields

Abstract: A field survey as well as market survey on Papaya mealybug, Paracoccus marginatus (Williams and Granara de Willink) was conducted in different regions of Bangladesh to know the infestation level, economic loss, and common management practices used by farmers to control this insect. Field survey revealed that more than one third of the papaya plants were affected by papaya mealybug and papaya growers faced a great economic loss. Severe infestation of papaya mealybug was also found in the nurseries of the survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The present study's findings are supported by Khan et al (2014) who stated that the infestation levels of papaya mealybug were varied in different seasons of the year, while high infestation was in March to June. Tairas et al (2014) observed that the population abundance of P. marginatus in the dry season was higher (3226 individuals/plant) than in the rainy season, which counted 285 individuals/plant.…”
Section: Effectiveness Of Different Treatments On Mealybug Infesting Leaf and Fruitsupporting
confidence: 86%
“…The present study's findings are supported by Khan et al (2014) who stated that the infestation levels of papaya mealybug were varied in different seasons of the year, while high infestation was in March to June. Tairas et al (2014) observed that the population abundance of P. marginatus in the dry season was higher (3226 individuals/plant) than in the rainy season, which counted 285 individuals/plant.…”
Section: Effectiveness Of Different Treatments On Mealybug Infesting Leaf and Fruitsupporting
confidence: 86%
“…2.1 Current global occurrence records of P. marginatus Global distribution points for P. marginatus were pooled from several publications, 5,6,9,11,[14][15][16][17][18][30][31][32][33][34][35] as well as a minority of unpublished sources. For papers with location information but without coordinate data, we geo-referenced the points based on the place names provided (data available in online repository).…”
Section: Methodsmentioning
confidence: 99%
“…4 Crop losses due to P. marginatus can have severe economic impactsone study found that infestations of papaya orchards in Bangladesh led to an average economic loss of approximately US$700 per hectare per year (range from US$413-1268). 5 Another study in Ghana showed that infestations in a papaya orchards led to a 65% yield loss, which resulted in reduced export earnings and the loss of jobs for 1700 people. 6 Thus, controlling the spread of P. marginatus has clear agricultural, economic and social benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insects may inhibit papaya growth, particularly from fruit set until harvest. Mealybug activity is highest in warm, dry weather (MAM Khan, 2014). Paracoccus marginatus is a native of Central America and spread to the Caribbean region and South America in the 1990s; since then it has accidentally been introduced to some islands in the Pacific region and some countries in Africa and Asia.…”
Section: Introductionmentioning
confidence: 99%